1997
DOI: 10.1172/jci119400
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human colon cancer cell growth by selective inhibition of cyclooxygenase-2.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
435
2
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(457 citation statements)
references
References 32 publications
13
435
2
7
Order By: Relevance
“…Celecoxib was obtained from Pfizer; MTT [3-(4,5- Cell Culture K562 cells were cultured in RPMI medium, supplemented with 10% FBS, 100 U/mL penicillin, 100 lg/mL streptomycin, and 3.0 Â 10 5 cells were added to each well on a 24-well plate, in triplicate. Celecoxib was diluted with DMSO (Sigma) in a 2-fold dilution series (10,20,40,80, and 160 lM). An equal volume of DMSO was added to control wells.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Celecoxib was obtained from Pfizer; MTT [3-(4,5- Cell Culture K562 cells were cultured in RPMI medium, supplemented with 10% FBS, 100 U/mL penicillin, 100 lg/mL streptomycin, and 3.0 Â 10 5 cells were added to each well on a 24-well plate, in triplicate. Celecoxib was diluted with DMSO (Sigma) in a 2-fold dilution series (10,20,40,80, and 160 lM). An equal volume of DMSO was added to control wells.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…Briefly, 200 lL (6 Â 10 4 cells) of a K562 cell suspension were plated in each well of a 96-well plate. After 12 hr, the cells were treated with varying concentrations of celecoxib (10,20,40,80, and 160 lM). An equal volume of DMSO was added to the control well, and the cells were cultured an additional 32 hr; then 20 lL MTT (5 mg/mL) in growth medium was added per well, and the plates incubated at 378C for 4 hr.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the expression of COX-2, one of the two isoforms of COX, is increased significantly in colonic neoplasms compared with normal colonic mucosa, and that COX-2 plays an integral role in colon cancer tumorigenesis and proliferation (Sheng et al, 1997;Sawaoka et al, 1998;Tsujii et al, 1998). However, the cellular and molecular mechanisms governing any possible relationship between gastrin and COX during GI tumour growth have not been elucidated.…”
mentioning
confidence: 99%
“…Pharmacologic inhibitors of EP4 suppress polyposis in the Apc min model (9), findings consistent with numerous other reports that selective cox-2 inhibitors inhibit polyp development, while administration of PGE2 accelerates their appearance and progression (8,9). These findings in animal models have been extended to studies in human colorectal cancer cell lines, where many of the downstream events of cox-2 inhibition and PGE2 signaling are more readily dissected (11). Taken together, the findings from preclinical models, cell culture and human clinical investigational studies provide a substantial foundation for exploring cox-2 dependent pathways and their intersection with other dominant genetic pathways for growth regulation in chemoprevention of CRC.…”
Section: Cyclooxygenases Aspirin and The Genetics Of Crc Chemoprevenmentioning
confidence: 85%